2020
DOI: 10.3390/beverages6030057
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Spirit Production from Coffee Cherries—Process Analysis and Sensory Evaluation

Abstract: Coffee fruit production is an important agricultural sector in more than 70 tropical countries. However, the production of fruit spirits based on coffee fruits has not been investigated to date. This study evaluated, for the first time, its fermentation and distillation performance, ethanol yield and sensorial attributes. A selected yeast strain (Saccharomyces cerevisiae L.) fermented coffee cherry mash within five days and produced ethanol concentrations of 31.0 g/L. The mash was distilled and distillate frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 30 publications
6
21
5
Order By: Relevance
“…The methanol content in the hearts fractions was 2600 ± 400 g/hL pa, which considerably exceeded the EU limit of 1000 g/hL pa and offers a safety margin of less than 2 for the level of acute toxicity of 5000 g/hL pa (see section 3). The authors suggested that the application of pectinase and the long storage had an adverse effect on the methanol concentration [15], which is plausible considering our review results in sections 4.1 and 4.2.…”
Section: Coffee Spirits -A Special Case For Methanol Mitigationsupporting
confidence: 59%
“…The methanol content in the hearts fractions was 2600 ± 400 g/hL pa, which considerably exceeded the EU limit of 1000 g/hL pa and offers a safety margin of less than 2 for the level of acute toxicity of 5000 g/hL pa (see section 3). The authors suggested that the application of pectinase and the long storage had an adverse effect on the methanol concentration [15], which is plausible considering our review results in sections 4.1 and 4.2.…”
Section: Coffee Spirits -A Special Case For Methanol Mitigationsupporting
confidence: 59%
“…Typically, stone fruits of the genus Prunus (cherries, plums) and pome fruits of the genera Malus and Pyrus (apples, pears) are associated with the highest methanol levels. More recently, coffee cherries (genus Coffea ) were identified as fruits possibly leading to comparably high methanol levels in their spirits [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Isobutanol did not show significant differences between the three fractions. Methanol indicated a typical behavior for batch distillation processes with no significant difference between its concentration in heads, hearts and tails [1,5,23]. 2-propanol and acetone were only detected in small quantities in the present study.…”
Section: Volatiles Compositionmentioning
confidence: 44%
“…In regard to the different mash volumes, juice mashes (No. [1][2][3][4][5][6] were distilled with a 20 L column still (Jacob Carl, Eislingen, Germany) [1], while fruit mash (No. 7-13) distillations were performed with a 120 L column still (Carl GmbH, Eislingen, Germany).…”
Section: Distillationmentioning
confidence: 99%
See 1 more Smart Citation